The attention/support to students in the socio-labor transition - Santana Vega, Lidia E. (2005)
In the present paper I intend to put forward some inquiries regarding the socio-labor guidance and transition of the young people in the co-ordinates of contemporary society. The outstanding paradox in which some young people are immersed when trying to get a first, second, third employment is also analyzed: "The job of looking for a job". This is a common experience shared by many young people when they try to find a place in the complex labor panorama. Looking for a job is a recurrent situation in contemporary society, given the high dose of precarious employment in which the productive world moves. Life-long jobs belong to the past and what is normal is that people strive to enter the competitive labor market repeatedly. Moreover, the paper offers the partial results of a larger research project that approaches tutorship, decision taking and expectations before the academic-labor future of the studentship in the last years of secondary school. Finally, I suggest some insights in the line that it is not longer feasible to work with old-fashioned guidance, trying to channel people's vocation and offering them information so that they get a job that provides them with the happiness of "doing what you like". Behind these ideas lay the normal biographies, the predictable itineraries. Labor market complexity makes the transition to working life very difficult. Once immersed in it, biographies and labor itineraries are constructed and reconstructed at the rhythm of the changing fortunes of times.
Keywords: Transition to working life; Guidance; Tutorship; Labor complexity; Trabajo; Orientación vocacional; Empleo de los jóvenes; Transición a la vida activa; Planificación laboral